HEPATITIS C VIRUS ANTIBODY PREVALANGE IN TURKIYE YUKSEK lHTlSAS HOSPITAL PERSONNEL - Ülkü SARITAŞ; B. YILDIRIM; N. KANTAROGLU; U. YILMAZ; E. ALTIPARMAK; G. SAYDAM; L. ONARAN (Turkish Journal of Gastroenterology, 2020)
-